VEGF inhibitors for anti-angiogenic therapy - Alitalo, Kari (Henry Stewart Talks, 2007)
Strategies to inhibit VEGFR signaling, Potential effects of inhibiting VEGF, Effects of anti-angiogenic therapy in preclinical models, Treatment of Human Xenograft Tumors With DC101, Combination Therapy with Anti-VEGFR-2 MAb and Gemcitabine, Examples of angiogenesis inhibitors in clinical trials, Inhibition of tumor lymphangiogenesis and lymph node metastasis with VEGFR-3-Fc
Archived at 2018/05/31